PROJETO DE EXTENSÃO “CÂMARA ESCURA: HISTÓRIAS E PRÁTICAS FOTOGRÁFICAS” - Scortegagna, Paulo E.; Oliveira, Stela M. Z. d.; Stefanello, Belair A.; Lizot, Eleandro; Bigolin, Áurea; Berno, Gládis; Pfeiffer, Jane W.; Donato, Sandra; Noll, Gisele C.; Karnikowski, Ulisses S.; et al. (Salão do Conhecimento, 2013)
Resumo